A New Approach that Eliminates Handling for Studying Aggression and the "Loser" Effect in Drosophila melanogaster - Trannoy, Severine (J Vis Exp, 2015)
Aggressive behavior in Drosophila melanogaster is composed of the sequential expression of stereotypical behavioral patterns (for analysis see (1)). This complex behavior is influenced by genetic, hormonal and environmental factors. As in many organisms, previous fighting experience influences the fighting strategy of flies and the outcome of later contests: losing a fight increases the probability of losing later contests, revealing "loser" effects that likely involve learning and memory (2-4). The learning and memory that accompanies expression of complex social behaviors like aggression, is sensitive to pre-test handling of animals (5,6). Many experimental procedures are used in different laboratories to study aggression (7-9), however, no routinely used protocol that excludes handling of flies is currently available. Here, we report a new behavioral apparatus that eliminates handling of flies, using instead their innate negative geotactic responses to move animals into or out of fighting chambers. In this protocol, small circular fight arenas containing a food cup are divided into two equal halves by a removable plastic slider prior to introduction of flies. Flies enter chambers from their home isolation vials via sliding chamber doors and geotaxis. Upon removal of plastic sliders, flies are free to interact. After specified time periods, flies are separated again by sliders for subsequent experimentation. All of this is done easily without handling of individual flies. This apparatus offers a novel approach to study aggression and the associated learning and memory, including the formation of "loser" effects in fly fights. In addition, this new general-purpose behavioral apparatus can be employed to study other social behaviors of flies and should, in general, be of interest for investigating experience-related changes in fundamental behavioral processes.